Experiences of barriers to self-monitoring and medication-management among Indian patients with type 2 diabetes, their primary family-members and physicians. (September 2022) - Chittem, Mahati; Sridharan, Subha Gomathy; Pongener, Matsungshila; Maya, Sravannthi; Epton, Tracy
Objectives: This study explored the subjective accounts of the main barriers to self-monitoring of blood-glucose (SMBG) and medication-management among Indian patients with type 2 diabetes (T2DM), their primary family-members (PFMs) and physicians. Methods: Using convenience sampling, patients with T2DM, their PFMs, and physicians, residing in a South Indian capital city, were recruited for semi-structured, audio-recorded interviews. Thematic analysis was used to analyze the data. Results: Fifty patients (female = 14; mean age = 42.5 years) and their PFMs (female = 38; mean age = 39 years), and 25 physicians (female = 4; mean age = 49.8 years) were recruited. Three superordinate themes were identified: (i) complex medication-regimen: confusion, forgetting and reduced motivation, (ii) family recommendations of alternative therapies due to the social pressures of avoiding stigma, intrusiveness and being misrepresented for injecting insulin, and (iii) an expensive illness: choosing to spend money on only medication. Discussion: Implications of the findings highlight the need to (i) train physicians in communication and empathy skills, (ii) empower patients to communicate their barriers to physicians through triadic communication models and question-prompt lists, (iii) educate communities on the benefits of insulin for managing T2DM to reduce stigma, and (iv) equip communities with information about health insurance to address the financial toll of T2DM management.